Awareness for People With Alzheimer’s Disease: Profiles and Weekly Trajectories - Mayelle, Amandine; Hazebrouck, Capucine; El Haj, Mohamad; Mograbi, Daniel C.; Antoine, Pascal (Frontiers in Aging Neuroscience, 2022)
Objective: We assessed the objects and processes of self- and disease-awareness in people with Alzheimer’s disease (AD). Then, we modeled fluctuations in awareness on a fortnightly basis. Method: Twenty-eight residents of nursing homes with a diagnosis of AD participated. They participated in four semistructured interviews at fortnight intervals. These interviews were cluster analyzed to determine profiles of awareness. A Markov chain was applied to model their weekly fluctuation(s). Results: Five profiles of awareness were observed that differed in terms of objects and processes. The profiles were relatively stable (P of .20 to .84). Interindividual variability in awareness was also observed through the numerous different individual trajectories that were identified. Discussion: Self- and disease-awareness are characterized by profiles that vary subtly between individuals. The weekly fluctuations in awareness underscore the need to employ assessment intervals that closely reflect daily life in institutions.